Development of Nutrition Education Media ‘Sugar-Sweetened Beverages’ Pocket Book for Elementary School - Tsabita, Khansa Mulita; Rahmawaty, Setyaningrum (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to develop nutrition education media in the form of a sugar-sweetened beverages pocketbook for elementary children and examining its validity. Methodology: The type of research used was research & development with 4 sequential steps including analysis, design, development, and evaluation its content va-lidity by 6 experts in the field of nutrition, language, and media. Results: The title of pocket book produced in this study was